Identification of Candidate Iron Transporters From the ZIP/ZnT Gene Families in the Mosquito Aedes aegypti - Tsujimoto, Hitoshi; Anderson, Michelle A. E.; Myles, Kevin M.; Adelman, Zach N. (Frontiers in Physiology, 2018)
Mosquito-transmitted viral pathogens, such as dengue and Zika, afflict tens of thousands of people every year. These viruses are transmitted during the blood-feeding process that is required for mosquito reproduction, the most important vector being Aedes aegypti. While vertebrate blood is rich in protein, its high iron content is potentially toxic to mosquitoes. Although iron transport and sequestration are essential in the reproduction of vector mosquitoes, we discovered that culicine mosquitoes lack homologs of the common iron transporter NRAMP. Using a novel cell-based screen, we identified two ZIP and one ZnT genes as candidate iron transporters in the mosquito Aedes aegypti, the vector of dengue, Zika and chikungunya. We determined organ-specific expression pattern of these genes at critical time points for early reproduction. The result indicates modulation of these genes upon blood feeding, especially, ZIP13 homolog that is highly up-regulated after blood feeding, suggesting its importance in iron mobilization during blood digestion and reproduction. Gene silencing resulted in differential iron accumulation in the midgut and ovaries. This study sets a foundation for further investigation of iron transport and control strategies of this viral vector.